Naevus count and MC1R R alleles contribute to melanoma risk. (1st November 2019) - Duffy, D.L.; Lee, K.J.; Jagirdar, K.; Pflugfelder, A.; Stark, M.S.; McMeniman, E.K.; Soyer, H.P.; Sturm, R.A.
Summary: Melanoma is the most dangerous form of skin cancer: around 15% of cases worldwide are fatal, but with early detection, survival rates are better than 95%. Having many large moles or having red hair increases a person's risk of developing melanoma; having certain versions of the MC1R gene, called R alleles, the main cause of red hair, also increases melanoma risk. This study, from Australia, aimed to find out if having both those risk factors increased melanoma risk more than the two risk levels simply added together. 611 people with melanoma and 656 who had never had melanoma donated a DNA sample, and researchers recorded the number of large moles, their skin and eye colour, and hair colour at age 21. The authors found that people with red hair and 20+ large moles were 10 times more likely to have melanoma than people with 0‐4 moles and dark brown hair. Looking specifically at the types of the MC1R gene that people carried, people with 20+ moles and MC1R R/R genotype were 25 times more likely to have melanoma than people with 0‐4 moles and MC1R wildtype/wildtype (consensus) genotype. While the R/R genotype, with or without the red hair phenotype, and a high mole count are both strong melanoma risk factors on their own, when combined they result in an extremely high‐risk profile for melanoma. The absolute lifetime risk to age 75 of getting melanoma in Australia is 23.3% for men and 19.3% for women who have 20+ moles and MC1R R/R genotype, compared to just 0.8% for men and 0.7% for women with 0‐4 moles and MC1R wildtype/wildtype genotype. This is higher than the risk threshold for screening in other cancers, so the authors suggest that people with many moles and red hair should be regularly checked for melanoma by a doctor, and that people with many moles but non‐red hair should also be checked to determine if they have an MC1R R/R genotype. Abstract : Linked Article: Duffy et al. Br J Dermatol 2019; 181 :1009–1016